2005
DOI: 10.1007/s10541-005-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death in Plants: Ultrastructural Changes in Pea Guard Cells

Abstract: Treatment with cyanide of epidermal peels isolated from pea leaves resulted in destruction of nuclei in the guard cells of stomata, which is visible with a light microscope. The process was accelerated by illumination. Electron microscopy revealed significant CN--induced changes in the ultrastructure of guard cells, which increased with time. Margination of chromatin, which is one of the first signs of apoptosis, was observed in the guard cells even after 1 h incubation of the isolated epidermis with CN-. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…D). The early detection of PCD by TEM compared with other microscopy techniques is in agreement with previous studies (Bakeeva et al , Dzyubinskaya et al ).…”
Section: Resultsmentioning
confidence: 99%
“…D). The early detection of PCD by TEM compared with other microscopy techniques is in agreement with previous studies (Bakeeva et al , Dzyubinskaya et al ).…”
Section: Resultsmentioning
confidence: 99%
“…In mature bracts, the presence of trichomes exhibiting degenerating protoplasts and cells with empty lumens corroborates the ephemeral nature of secretory activity. The occurrence of chromatin condensation, as well as darkening and fragmentation of the cytoplasm due to swelling of endoplasmic reticulum, were previously considered as evidence of programmed cell death in plants [ 13 , 62 , 63 ], and indicate that a comparable process operates on the secretory indumentum of T. cyanea . In this context, the occurrence of vesiculation throughout the cytoplasm can be interpreted as profuse dilations of the endoplasmic reticulum rather than due to vacuome development.…”
Section: Discussionmentioning
confidence: 99%
“…The traits described for cell death that were observed in this study indicate that it may be a vacuolar cell death, which is manifested by a gradual decrease in the volume of cytoplasm and a significant increase in the vacuole volume as well as volume presence of the cytoplasm content of the cells inside the vacuole compartment and the subsequent degradation of the cargo [ 40 ]. This type of cell death was also described during embryo development as well as during tissue and organ differentiation, which is either a normal part of the plant developmental program or a response to stressful conditions [ 41 , 42 , 43 , 44 , 45 ]. Interestingly, in our research, we observed the increasing number of plastoglobuli, which may be linked with the upregulation of plastid lipid metabolism in response to oxidative stress provoked by 5-azaC.…”
Section: Discussionmentioning
confidence: 99%